2016
DOI: 10.1177/2150135116668834
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian Cardiology and Cardiac Surgery in Sub-Saharan Africa

Abstract: The current model of collaboration has brought cardiac care to patients having cardiac diseases. However, the model appears to be suboptimal for skill transfer. The model needs to be reshaped to achieve this complex goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…This is the most frequently used model and the easiest to use. It is expensive and the local training has been shown to be ineffective and suboptimal for skill transfer ( 9 ), and entirely dependent on donations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the most frequently used model and the easiest to use. It is expensive and the local training has been shown to be ineffective and suboptimal for skill transfer ( 9 ), and entirely dependent on donations.…”
Section: Discussionmentioning
confidence: 99%
“…In Cameroon, 45% of the population is under 15 years of age, as expressed in Table 1 the birth rate of Cameroon is 36.2‰ with an infant mortality of 63‰, the life expectancy is 54.8 years for males and 57.1 years for females ( 9 ).…”
Section: Cameroonmentioning
confidence: 99%
“…Data analysis: The collected data were analyzed using descriptive and inferential statistics. Statistical package for social sciences (SPSS) version 22 software was used to analyze the data.Frequencies and percentages were used to present categorical data. Parametric tests were used to assess the association between variables and outcome.…”
Section: Settingmentioning
confidence: 99%
“…Treatment of CHD in most parts of Africa, including Ethiopia, is provided by overseas voluntary mission or humanitarian aid, and the majority of the patients do not have access to the service. Success of such treatment models in sustaining the care has been questioned, and reconsideration was suggested (22,23).Global call for coordination of such pediatric cardiac surgery mission efforts was also recommended (24). Evidence on CHD related SAM is scarce from Africa and absent from Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to discern how many of the host units have become self-reliant. This was highlighted in a study of 26 medical missions in sub-Saharan Africa (13). The authors concluded that the current model of collaboration via short term medical missions appears sub optimal for skill transfer and suggested deeper involvement of universities, governmental institutions, and visiting teams.…”
Section: Short Term Medical Missionsmentioning
confidence: 94%